2021
DOI: 10.5433/1679-0359.2021v42n6supl2p3707
|View full text |Cite
|
Sign up to set email alerts
|

Development and production of maize as a function of biochar rates

Abstract: Poultry litter biochar has shown to be promising in crop development and production. On this basis, this study was developed to investigate the influence of increasing rates of poultry litter biochar on the growth and production of maize hybrid BRS 2022. The experiment was laid out in a completely randomized design with six biochar rates (0, 2.0, 4.0, 6.1, 8.1 and 10.1 t ha-1) and four replicates. Plots consisted of pots with a volume of 20 dm3, with one plant each. The following variables were evaluated at 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, regarding the study of heavy metals adsorption by biochar, it was observed in these same samples that biochar increased zinc adsorption after this same incubation period (Lima et al, 2017). Likewise, the presence of biochar in the soil influences the adsorption of cadmium (Chaves et al, 2021) and increases soil fertility, influencing the growth, development, and yield of crops (Mendes et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, regarding the study of heavy metals adsorption by biochar, it was observed in these same samples that biochar increased zinc adsorption after this same incubation period (Lima et al, 2017). Likewise, the presence of biochar in the soil influences the adsorption of cadmium (Chaves et al, 2021) and increases soil fertility, influencing the growth, development, and yield of crops (Mendes et al, 2021).…”
Section: Resultsmentioning
confidence: 99%